Impact of maternal pharmacotherapy use during lactation on breastfeeding options and safety - Anna Czuba; Julia Dubel; Martyna Zielnik; Klaudia Serafin; Pola Knurowska; Patrycja Rembisz (Quality in Sport, 2024)
Due to its unique composition, breast milk is the ideal food for the baby, as it contains all the necessary nutrients. Breastfeeding is recommended by numerous scientific societies and is associated with many immediate as well as long-term benefits for mother and child. The use of pharmacotherapy in mothers during lactation raises concerns about the adverse consequences of treatment and the health of the child due to the distribution of drugs into breast milk. The following paper aims to present the safety profile of selected drug products during breastfeeding.